Testing The Efficiency of the Damascus Stock Exchange MARKET at The Weak level using Random walking - معلا سلمان (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The research aims to test The Efficiency of the Damascus Stock Exchange Market according to the random walk hypothesis at the weak level, and thus measure the extent to which some investors can achieve normal returns using statistical tests. The study found a number of result: - Damascus Stock Exchange Market is considered inefficient at the weak level of efficiency. - There is a possibility of achieving unusual returns by some investors.